Use of Supplementary Irrigation for Improvement of Growth and Yield of Sorghum [Sorghum bicolor (L.) Monech] in North Darfur State (University of Khartoum Journal of Agricultural Sciences, 2025)
A field experiment was conducted in two consecutive seasons(2006 and 2007) in Al-Fashir University Farm in North Darfur State toinvestigate the impact of supplementary irrigation at three available waterdepletion levels (AWDL); namely, 25%, 50% and 75% on growth and yieldof two sorghum varieties (Wad Ahmed and Tabat) grown on a fine loamy,mixed isohyperthermic Typic Haplocambid. The experimental design was asplit-plot design with four replicates. Irrigation treatments were designatedthe main plots and varieties the subplots. In both seasons, Wad Ahmedvariety was significantly better than Tabat in germination percentage, plantheight, leaf area index and number of heads. For the two seasons, the meanplant height, leave area index and number of heads ranged from 147.0 to173.5 cm, 3.3 to 7.4 and 77 to 158, respectively. In the two successiveseasons, the mean dry matter yield was 11.2 and 12.8 ton/ha for WadAhmed and 7.9 and 9.9 ton/ha for Tabat. In both seasons, the mean thousandgrain weight and grain yield ranged from 26.0 to 29.59 g and from 6.2 to 9.4ton/ha. Wad Ahmed gave significantly (P = 0.05) greater yield than Tabat inthe first season, but the difference was not significant in the second season.Furthermore, in most cases, application of water at 25% AWDL gave bettergrowth and yield than at 50% or 75%. However, the impact of AWDL wasnot significant because of the random variation of occurrence and quantityof rainfall. The Experiment showed that supplementary irrigation, usingharvested water, offers a great potential for improving crop production inNorth Darfur State.
Keywords: Water harvesting; supplementary irrigation; sorghum; Darfur